Olfactory response in caterpillars of Pieris rapae for host recognition - Schön, Tomas (SLU/Dept. of Ecology, 2011)
Plants interact with phytophagus insects through release of volatile chemical compounds. They can either function as a defense against herbivores by attracting predators and parasitoids, or they can act as an attractant for the herbivores themselves. This knowledge is important and could be applied in agricultural science to develop novel strategies for pest control. The plant-insect interaction was studied using three genotypes of the Brassicaceae family and the small cabbage butterfly, Pieris rapae. The experiment was conducted by placing larvae in a four-way olfactometer to see what potential feeding preferences it showed when choosing between the odor of 1) the three genotypes and 2) different treatments on each of the genotypes. The treatments tested were; undamaged plant, plants with larvae induced damage, frass and air as a control choice. One treatment experiment was made for each of the plant genotypes. The prediction was that larvae would show preferences for either i) damaged plants since the release of volatiles from these are more abundant that from undamaged plants, or ii) frass, since this emit nitriles which acts as an attractant for phytophagus insects. The result however showed no significant preference for either genotype or treatment, except for the treatment of cauliflower where the larvae seem to prefer the odor of damaged plants over that of the control choice. A number of volatiles are released exclusively or occur at higher concentration in the headspace of damaged cauliflower than in damaged plants of the other genotypes. This is what makes the cauliflower blend of volatiles unique and is most likely what attracts the larvae to it.